Examining the Role of Cognitive Workload, Professional Competence, and Intrinsic Motivation in Teacher Job Satisfaction - Roni Matthew Nahampun; Abd. Rasyid Syamsuri; Sharnuke Asrilsyak (International Journal of Science and Environment (IJSE), 2026)
This study aims to examine the influence of cognitive workload, professional competence, and intrinsic motivation on teacher job satisfaction at SMA Negeri 16 Batam. The population of this study consisted of all certified teachers at SMA Negeri 16 Batam. A total sampling technique was employed, involving all 37 teachers as research respondents. The study applied a quantitative approach using multiple linear regression analysis with the support of SPSS SmartPLS version 4. The findings reveal that cognitive workload has a negative and significant effect on teacher job satisfaction, whereas professional competence and intrinsic motivation have positive and significant effects on teacher job satisfaction. Furthermore, cognitive workload, professional competence, and intrinsic motivation simultaneously have a significant influence on teacher job satisfaction. These findings suggest that schools should implement effective workload management, enhance teachers’ professional competencies through continuous professional development programs, and strengthen intrinsic motivation in order to improve teacher job satisfaction and overall educational quality.